Simple Method for Quantitative Evaluation of Surface Smoothness of Wood - Shukla, K. S.; Pant, B. C. (Indian Forester, 1985)
A simple method for measuring the smoothness of planed or sanded wood surface quantitatively is suggested with detailed diagrams. In this method, co-efficient of fricyion of planed wood is measured with respect to rubber and surface smoothness worked out. Using this technique surface smoothness of 47 indian timbers has been evaluated and compared with the smoothness of taek specimen planed under identical conditions. Surface smoothness measured along the axial growth direction of the tree and opposite, to it, of black chuglam specimens planed after setting cutter at 15°, 20°, 25° and 30° is also reported. Best planed surface was obtained along growth directions with 30° cutting angles which talleys with the earlier findings on the same aspects following ASTM method. Further work on the stabdardisation of this technique is suggested.